Water-soluble quenching medium and preparation method thereof
By using components such as polyalkylene glycol in the water-soluble quenching medium and adding anti-rust agents such as potassium phosphate, boric acid and modified sodium silicate, the problem of insufficient quenching cooling speed and anti-rust performance in the prior art is solved, and efficient cooling and excellent anti-rust effect are achieved.
Patent Information
- Application Number
- CN202411671643.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
The existing water-soluble quenching media have shortcomings in terms of quenching cooling speed and rust-proof performance, and it is difficult to improve the cooling speed and rust-proof effect at the same time.
A water-soluble quenching medium consisting of polyalkylene glycol, polyacrylamide, sodium polyacrylate, carboxymethylcellulose, anti-rust agent, etc. is used to regulate the heat exchange process by adjusting the polypropylene glycol and Tween 80, and the potassium phosphate, boric acid and modified sodium silicate in the anti-rust agent form a dense protective film to improve the anti-rust performance.
The quenching cooling speed and rust resistance are significantly improved, forming a stable heat exchange interface layer, optimizing the heat exchange process, ensuring uniform heat dispersion, preventing metals from being damaged due to excessive cooling, and forming an effective anti-rust protection film.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quenching water agents, and in particular to a water-soluble quenching medium and a preparation method thereof. Background Art
[0002] Water-soluble quenching medium is a substance or mixture that can dissolve in water and change the cooling characteristics of water to meet the quenching requirements of different metal materials. Its characteristics include adjusting the cooling rate to reduce the tendency of workpiece deformation and cracking, achieving uniform cooling to improve quenching quality and performance uniformity, being clean and environmentally friendly, safe to use and not easy to burn. It is mainly used in the quenching treatment of various steel materials and non-ferrous metals. For example, in the manufacture of mechanical parts, the quenching process of key components such as gears, shafts, springs, etc. of automobiles, ships, and aircraft can use water-soluble quenching media to obtain different combinations of hardness, strength and toughness to meet the use requirements of different workpieces.
[0003] In the study of rust prevention performance, water-soluble quenching medium can be added with cooling rate regulator, rust inhibitor, defoamer, alkalinity retainer and potassium hydroxide and other ingredients. By forming a multiple passivation layer protective film on the surface of the metal workpiece, the metal is isolated from air and water, the metal activity is weakened, the oxidation and rust rate is slowed down, and it still has good rust prevention when diluted at low concentration, reducing the amount and cost of quenching medium. In terms of improving the quenching cooling rate performance, for example, adding inorganic substances such as sodium chloride and sodium hydrogen nitrite can destroy the steam film and increase the cooling rate of water in the high temperature zone. For example, adding supersaturated nitrates in the high temperature zone destroys the formation and stability of the steam film, and the cooling rate is close to water. In the low temperature zone, due to the high concentration and high viscosity of the solution, the cooling rate is close to oil, and the quenched parts have good rust prevention. There are also new polymer water-soluble quenching agents in the prior art. The cooling capacity can be adjusted in a wide range by adjusting the concentration, etc., to obtain a cooling rate between water and oil and equivalent to oil or slower.
[0004] CN102417955A discloses a water-soluble quenching medium for hot die steel, which is prepared by uniformly mixing polyalkylene glycol, polyvinyl pyrrolidone, rust inhibitor, bactericide, pH regulator, sedimentation agent, defoamer and water according to a proportion. The production cost is low, the product is non-flammable and environmentally friendly. The product can replace the oil quenching medium and fully meet the quenching requirements of hot die steel represented by 4Cr5MoSiV1, 5CrMnMo and 5CrNiMo. The rust inhibitor added in the invention can not improve the rust prevention performance and quenching speed at the same time.
[0005] CN102605150A discloses a quenching liquid and a quenching process for improving the hardening thickness of 50CrVA spring steel. The organic polymer water-soluble quenching liquid used in the invention is a water-soluble solution composed of a liquid organic polymer and a corrosion inhibitor. The organic polymer is completely soluble in water to form a clear and homogeneous solution. The organic polymer water-soluble quenching liquid is used to replace rapid oil or diesel quenching, which saves rapid oil or diesel, not only reduces production costs, but also protects the production environment and natural resources. The quenching liquid of the invention does not solve the problems of rust prevention performance and improving quenching speed at the same time. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the quenching cooling speed and the rust prevention performance of the water-soluble quenching medium.
[0007] To achieve the above object, the present invention provides a water-soluble quenching medium and a preparation method thereof.
[0008] The water-soluble quenching medium comprises the following components in parts by weight:
[0009] 40-50 parts of polyalkylene glycol, 8-12 parts of polyacrylamide, 15-25 parts of rust inhibitor, 4-10 parts of sodium polyacrylate, 4-8 parts of carboxymethyl cellulose, 2-4 parts of polypropylene glycol, 1-2 parts of Tween 80, and 0.2-0.6 parts of disodium ethylenediaminetetraacetate.
[0010] The rust inhibitor preparation method is as follows:
[0011] Add water-soluble phosphate and borax into water, stir at room temperature, add sodium nitrite and silicate to disperse, and obtain a rust inhibitor after drying.
[0012] The preparation method of the rust inhibitor is as follows, in parts by weight:
[0013] Add 6-8 parts of water-soluble phosphate and 2-4 parts of borax to 180-220 parts of water, stir at room temperature for 0.5-1 hour, add 4-8 parts of sodium nitrite and 2-6 parts of silicate, ultrasonically disperse for 15-30 minutes, and dry to obtain a rust inhibitor.
[0014] The water-soluble phosphate is one or more of sodium phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium phosphate, potassium dihydrogen phosphate, and sodium magnesium phosphate.
[0015] The silicate is one of sodium silicate and modified sodium silicate.
[0016] The preparation method of the modified sodium silicate is as follows:
[0017] Sodium silicate is added to water and stirred, vinyltrichlorosilane is added, oxalic acid aqueous solution is added dropwise to adjust the pH, the mixture is stirred, and concentrated and dried to obtain modified sodium silicate.
[0018] The preparation method of the modified sodium silicate is as follows, in parts by weight:
[0019] Add 14-16 parts of sodium silicate to 200-300 parts of water and stir for 0.5-1 hour, add 4-8 parts of vinyltrichlorosilane, drop oxalic acid aqueous solution to adjust the pH to 4-5, stir at 60-70°C for 3-4 hours, concentrate and dry to obtain modified sodium silicate.
[0020] The oxalic acid aqueous solution is a 1-2wt% oxalic acid aqueous solution.
[0021] A method for preparing a water-soluble quenching medium comprises the following steps:
[0022] The water-soluble quenching medium is obtained by mixing polyalkylene glycol, polyacrylamide, sodium polyacrylate, carboxymethyl cellulose, rust inhibitor, polypropylene glycol, Tween 80 and disodium ethylenediaminetetraacetate.
[0023] The water-based quenching medium of the present invention is mainly composed of polyalkylene glycol, and its good thermal conductivity ensures that heat can be quickly transferred from the hot metal to the quenching medium, so that the metal can be cooled quickly. At the same time, the water-soluble medium can also adjust the fluidity of the solution, ensure that the heat is evenly dispersed in the solution, and maintain a stable and efficient cooling rate. Polyacrylamide and sodium polyacrylate can control the heat transfer rate by changing the rheological properties of the solution, prevent the metal from deforming and cracking due to excessive heat transfer in the early stage of quenching, and ensure that the heat is continuously and stably transferred to ensure uniform cooling. It can also stabilize the performance of the solution, prevent other components from agglomerating at high temperatures, and ensure that the quenching process is carried out smoothly. Carboxymethyl cellulose can form a heat exchange interface layer on the surface of the steel during quenching, play a temperature buffering role, avoid damage to the metal due to excessive instantaneous cooling, ensure continuous heat transfer and cooling, and promote heat exchange to optimize the quenching process. Polypropylene glycol and Tween 80 quenching medium help optimize the heat exchange process, adjust heat capacity and thermal conductivity, prevent bubbles from being generated, ensure that heat exchange is carried out evenly, and enable the quenching medium aqueous solution to better absorb and transfer heat, thereby ultimately increasing the cooling rate. Disodium EDTA can complex metal ions during the quenching process, keep the solution clear and stable, prevent metal ion precipitation from affecting heat conduction, facilitate smooth heat transfer and cooling process, and achieve a stable cooling rate.
[0024] The rust inhibitor of this aspect wraps potassium phosphate and boric acid through modified sodium silicate or sodium silicate and acts on the metal surface during application, and cooperates with the action of each substance to form a dense and stable protective film. Among them, borax can be hydrolyzed in aqueous solution to produce borate ions, and borate ions may react with the metal surface to form a borate protective film, thereby enhancing the corrosion and rust prevention ability of the metal surface. Sodium nitrite has an anti-rust effect in the quenching medium aqueous solution, and can form a protective film on the metal surface to prevent oxygen and water from contacting the metal, and improve the density and stability of the film. When acting together with modified sodium silicate and potassium phosphate, multiple protective mechanisms synergize and further improve the anti-rust performance. The phosphate ions produced by the hydrolysis of potassium phosphate may react with the metal surface to form a relatively thin phosphate protective film, which can isolate the metal from the external environment to a certain extent and slow down the occurrence of corrosion reactions. In the preparation of modified sodium silicate, the silanol groups generated by the hydrolysis of vinyltrichlorosilane react with the silicate ions of sodium silicate, and organic groups are introduced into the structure of sodium silicate, which changes the surface properties of sodium silicate and improves its adsorption and film-forming properties on the metal surface. At the same time, the modified sodium silicate wraps and adheres potassium phosphate and borax when forming a protective layer. After drying, the rust inhibitor formed can form a stronger interaction with the metal surface, thereby enhancing the density and stability of the protective layer and improving the rust prevention protection of the quenching medium on the metal.
[0025] Beneficial effects of the present invention:
[0026] 1. Compared with the prior art, the water-soluble quenching medium of the present invention has polyalkylene glycol as the main component, which has good thermal conductivity and can adjust the fluidity of the solution. It can quickly transfer heat from the hot metal and ensure that the heat is evenly dispersed. At the same time, it uses the synergistic effect of various additives such as polyacrylamide, sodium polyacrylate, carboxymethyl cellulose, and rust inhibitors to form a stable heat exchange interface layer. The ester optimizes the heat exchange process and prevents the generation of bubbles, and together achieves excellent quenching performance. For example, potassium phosphate in the rust inhibitor can improve the thermal conductivity and fluidity of the solution and accelerate heat transfer. Sodium silicate in the rust inhibitor forms a protective layer on the metal surface with potassium phosphate and boric acid, forming a multi-level, multi-component protection system, which jointly adjusts the thermal conductivity, specific heat capacity and other thermophysical parameters of the solution, and may also affect the fluidity, surface tension and other properties of the solution, thereby significantly improving the quenching speed.
[0027] 2. Compared with the prior art, the invention adds a specific rust inhibitor, and potassium phosphate and borax are wrapped by sodium silicate or modified sodium silicate and act on the metal surface to form a dense and stable protective film, wherein the borate ions generated by the hydrolysis of borax form a borate protective film to enhance the metal's corrosion and rust resistance, sodium nitrite improves the density and stability of the film, potassium phosphate forms a phosphate protective film to isolate the metal from the external environment, and the introduction of sodium silicate or modified sodium silicate allows the rust inhibitor to be adsorbed and film-formed on the metal surface. The rust inhibitor of the invention significantly improves the rust prevention performance through the synergistic effect of multiple components. DETAILED DESCRIPTION
[0028] The parameters of the specific chemical substances used in the examples are from the following sources:
[0029] Polyalkylene glycol: Brand is GEO Specialty Chemicals Co., Ltd., model is GEOlube ® TB150.
[0030] Polyacrylamide: density is 1.302g / cm 3 , molecular weight is 710,700, manufacturer is Jinan Shanhai Chemical Technology Co., Ltd., model is non-ionic.
[0031] Sodium polyacrylate: molecular weight is 2000-5000, the manufacturer is Zouping Delin New Material Technology Co., Ltd., model is Derin42N.
[0032] Vinyltrichlorosilane: CAS number: 75-94-5.
[0033] Polypropylene glycol: molecular weight is 1800-2200, pH is 5-7, the manufacturer is Jiangsu Hai'an Petrochemical Plant, model is PPG-2000.
[0034] Example 1
[0035] A method for preparing a water-soluble quenching medium comprises the following steps:
[0036] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0037] Example 2
[0038] A method for preparing a water-soluble quenching medium comprises the following steps:
[0039] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 18 g of potassium phosphate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0040] Example 3
[0041] A method for preparing a water-soluble quenching medium comprises the following steps:
[0042] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 18 g of sodium silicate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0043] Example 4
[0044] A method for preparing a water-soluble quenching medium comprises the following steps:
[0045] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 18 g of modified sodium silicate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0046] The preparation method of the modified sodium silicate is as follows:
[0047] 15 g of sodium silicate was added to 240 g of water and stirred for 0.5 hour. 6 g of vinyltrichlorosilane was added, and 1 wt % oxalic acid aqueous solution was added dropwise to adjust the pH to 4.5. The mixture was stirred at 65° C. for 4 hours and concentrated to dryness to obtain modified sodium silicate.
[0048] Example 5
[0049] A method for preparing a water-soluble quenching medium comprises the following steps:
[0050] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 11 g of potassium phosphate, 7 g of sodium silicate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0051] Example 6
[0052] A method for preparing a water-soluble quenching medium comprises the following steps:
[0053] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 11 g of potassium phosphate, 7 g of modified sodium silicate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0054] The preparation method of the modified sodium silicate is as follows:
[0055] 15 g of sodium silicate was added to 240 g of water and stirred for 0.5 hour. 6 g of vinyltrichlorosilane was added, and 1 wt % oxalic acid aqueous solution was added dropwise to adjust the pH to 4.5. The mixture was stirred at 65° C. for 4 hours and concentrated to dryness to obtain modified sodium silicate.
[0056] Example 7
[0057] A method for preparing a water-soluble quenching medium comprises the following steps:
[0058] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 7 g of potassium phosphate, 2 g of borax, 5 g of sodium nitrite, 4 g of modified sodium silicate, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0059] The preparation method of the modified sodium silicate is as follows:
[0060] 15 g of sodium silicate was added to 240 g of water and stirred for 0.5 hour. 6 g of vinyltrichlorosilane was added, and 1 wt % oxalic acid aqueous solution was added dropwise to adjust the pH to 4.5. The mixture was stirred at 65° C. for 4 hours and concentrated to dryness to obtain modified sodium silicate.
[0061] Example 8
[0062] A method for preparing a water-soluble quenching medium comprises the following steps:
[0063] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 18 g of rust inhibitor, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0064] The rust inhibitor preparation method is as follows:
[0065] 7 g potassium phosphate and 3 g borax were added to 200 g water, stirred at room temperature for 0.5 hour, 6 g sodium nitrite and 4 g modified sodium silicate were added, ultrasonically dispersed for 20 minutes, and dried to obtain a rust inhibitor.
[0066] The preparation method of the modified sodium silicate is as follows:
[0067] 15 g of sodium silicate was added to 240 g of water and stirred for 0.5 hour. 6 g of vinyltrichlorosilane was added, and 1 wt % oxalic acid aqueous solution was added dropwise to adjust the pH to 4.5. The mixture was stirred at 65° C. for 4 hours and concentrated to dryness to obtain modified sodium silicate.
[0068] Example 9
[0069] A method for preparing a water-soluble quenching medium comprises the following steps:
[0070] 45 g of polyalkylene glycol, 10 g of polyacrylamide, 5 g of sodium polyacrylate, 6 g of carboxymethyl cellulose, 18 g of rust inhibitor, 3 g of polypropylene glycol, 1 g of Tween 80, and 0.5 g of disodium ethylenediaminetetraacetate are mixed to obtain the water-soluble quenching medium.
[0071] The rust inhibitor preparation method is as follows:
[0072] Add 7g potassium phosphate and 3g borax to 200g water, stir at room temperature for 0.5 hour, add 6g sodium nitrite and 4g sodium silicate, ultrasonically disperse for 20 minutes, and obtain a rust inhibitor after drying.
[0073] Test Example 1
[0074] The water-soluble quenching medium prepared by the preparation method of Examples 1-9 was added to water at a ratio of 5% to obtain a quenching medium aqueous solution for anti-rust performance testing. The test was based on the industry standard JB / T 13025-2017 "Polyalkylene glycol (PAG) water-soluble quenching medium for heat treatment". The test data are summarized in Table 1, and the anti-rust performance classification is shown in Table 2.
[0075]
[0076] The scheme of Example 1 contains polyalkylene glycol, polyacrylamide, sodium polyacrylate, carboxymethyl cellulose, polypropylene glycol, Tween 80, and disodium ethylenediaminetetraacetic acid, and the basic ingredients have limited anti-rust protection effects. Examples 2-4 respectively add potassium phosphate, sodium silicate, and modified sodium silicate as rust inhibitor components on the basis of Example 1. The potassium phosphate added in Example 2 can improve the anti-rust performance and reduce the area of rust spots, but there are limitations in protection, and there is still a certain degree of rust. The sodium silicate added in Example 3 can form silicate gel or precipitation in the quenching medium aqueous solution. Some silicate ions may be adsorbed on the metal surface to play a physical barrier role, preventing corrosive media such as oxygen and moisture from penetrating into the metal, but the protective layer formed is not uniform or firm enough, and cannot completely prevent the occurrence of rust. Example 4 modifies sodium silicate on the basis of Example 3. The protective layer formed by the modified sodium silicate on the metal surface in the quenching medium aqueous solution is more effective, which can better prevent the formation of rust spots, and the number and size of rust spots are significantly reduced.
[0077] In Examples 5 and 6, sodium silicate, modified sodium silicate and potassium phosphate are compounded for use respectively. The synergistic complementary effect enhances the protection of the metal surface to a certain extent. The modified sodium silicate enhances the binding force between the modified sodium silicate and the metal surface, and potassium phosphate also contributes to the stability of film formation, making the protective effect better than that of Example 5.
[0078] The difference between Examples 8 and 9 and Example 7 is that potassium phosphate, borax and sodium nitrite are combined with modified sodium silicate and sodium silicate for modification, respectively, and then added to the quenching medium as rust inhibitors; the reason why the rust prevention effect of Examples 8-9 is better than that of Example 7 is that: the phosphate protective film formed by the phosphate ions generated by the hydrolysis of potassium phosphate alone in the quenching medium aqueous solution is thin, and has limited density and stability; the borate protective film formed by the borate ions generated by the hydrolysis of borax alone in the quenching medium aqueous solution is insufficient in terms of comprehensiveness and durability of protection; sodium nitrite added alone is alkaline in the quenching medium aqueous solution, making it easier for sodium silicate to decompose in the alkaline quenching medium aqueous solution to obtain active silicate ions, but the components in the quenching medium aqueous solution are dispersed separately, without cross-correlation and working together.
[0079] Example 8-9 Potassium phosphate and boric acid are wrapped by modified sodium silicate or sodium silicate and act on the metal surface in the application, and the action of each substance is coordinated to form a denser protective film, wherein sodium nitrite adjusts the pH to accelerate the film formation of modified sodium silicate or sodium silicate. Example 8 The synergistic effect of the rust inhibitor composed of potassium phosphate, borax, sodium nitrite and modified sodium silicate achieves excellent anti-rust effect. By forming a dense and stable protective film on the metal surface, it can effectively prevent oxygen, moisture and other corrosive media from contacting the metal, wherein borax can be hydrolyzed in aqueous solution to produce borate ions, and borate ions may react with the metal surface to form a borate protective film, enhancing the corrosion and rust resistance of the metal surface, and sodium nitrite helps to improve the density and stability of the film. When acting together with modified sodium silicate and potassium phosphate, multiple protection mechanisms synergize and further improve the anti-rust performance. The phosphate ions produced by the hydrolysis of potassium phosphate may react with the metal surface to form a relatively thin phosphate protective film, which can isolate the metal from the external environment to a certain extent and slow down the occurrence of corrosion reactions. The difference between Example 8 and Example 9 is that the modified sodium silicate is modified by reacting the silanol group generated by the hydrolysis of vinyltrichlorosilane with the silicate ion of sodium silicate, introducing an organic group into the structure of sodium silicate, thereby changing the surface properties of sodium silicate and improving its adsorption and film-forming properties on the metal surface; at the same time, when forming a protective layer, the modified sodium silicate wraps and adheres potassium phosphate and borax, and after drying, the rust inhibitor formed can form a stronger interaction with the metal surface, thereby enhancing the density and stability of the protective layer and improving the rust prevention protection of the quenching medium on the metal.
[0080] Test Example 2
[0081] The water-soluble quenching medium prepared by the preparation method of Examples 1-8 was added to water at a ratio of 5% to obtain a quenching medium aqueous solution, which was applied to the surface quenching of 40CrMo steel. The test was carried out at 500°C. The test was based on the industry standard JB / T 13025-2017 "Polyalkylene glycol (PAG) water-soluble quenching medium for heat treatment". The test data are summarized in Table 3.
[0082] There are differences in the quenching cooling performance data in Test Example 2, and the main reason is related to the different components of the quenching medium in each embodiment, which affect the cooling rate through different principles. Example 1 is a basic formula, in which polyalkylene glycol quickly absorbs and transfers the heat of steel through good thermal conductivity and adjusts the fluidity of the solution to ensure uniform heat dispersion; polyacrylamide and sodium polyacrylate change the rheological properties of the solution, control the heat transfer rate, stabilize the solution performance, and prevent component agglomeration; carboxymethyl cellulose forms a heat exchange interface layer, slows down the initial heat transfer rate and adapts to temperature changes, while improving the wettability of the solution; polypropylene glycol and Tween 80 synergistically optimize the heat exchange process, adjust heat capacity and thermal conductivity, form a stable emulsion system and prevent bubble formation; disodium ethylenediaminetetraacetic acid complexes metal ions to keep the solution clear and stable and stabilize the chemical environment. The synergistic effect of each component achieves a stable cooling rate.
[0083] In Examples 2-4, potassium phosphate, sodium silicate, and modified sodium silicate are added to Example 1, respectively. Potassium phosphate can improve the thermal conductivity and fluidity of the solution, accelerate the transfer of heat, and help to increase the cooling rate. The sodium silicate added in Example 3 increases the viscosity of the solution, hinders heat transfer, and causes the cooling rate to be lower than the basic formula of Example 1. In Example 4, sodium silicate is modified, and the cooling rate is higher than that of the unmodified Example 3, but lower than that of Example 2.
[0084] In Examples 5-6, potassium phosphate is compounded with sodium silicate and modified sodium silicate, respectively. It can be seen that the compound use of potassium phosphate and sodium silicate reduces the potassium phosphate concentration compared with Example 2, and the cooling rate is lower than that of Example 2; In Example 6, the compound use of potassium phosphate and modified sodium silicate can play a synergistic effect, optimize heat exchange, and the cooling rate is higher than that of Example 2 and Example 4 in which only potassium phosphate and modified sodium silicate are added.
[0085] In Examples 7-8, multiple components are added to synergistically change the thermophysical properties of the solution, and the cooling rate is improved. Among them, Example 7 is the separate addition of multiple components, and Example 8 makes the multiple components into a complete whole and then adds them. Potassium phosphate can form a phosphate protective film and affect the thermal conductivity and specific heat capacity of the solution. Borax is hydrolyzed to produce borate ions, which enhance the metal's corrosion resistance and interact with other components. Sodium nitrite adjusts the pH to promote the hydrolysis reaction. The introduction of modified sodium silicate synergistically forms a dense protective film on the metal surface. Finally, the thermal conductivity, specific heat capacity and other thermophysical parameters of the solution are jointly adjusted through the interaction of the components. At the same time, the synergistic effect between the components may also affect the fluidity, surface tension and other properties of the solution, thereby further optimizing the heat exchange process and improving the maximum cooling rate.
[0086] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A water-soluble quenching medium, characterized in that: It comprises the following components in parts by weight: 40-50 parts of polyalkylene glycol, 8-12 parts of polyacrylamide, 15-25 parts of rust inhibitor, 4-10 parts of sodium polyacrylate, 4-8 parts of carboxymethyl cellulose, 2-4 parts of polypropylene glycol, 1-2 parts of Tween 80, and 0.2-0.6 parts of disodium ethylenediaminetetraacetate; The preparation method of the rust inhibitor is as follows, in parts by weight: Add water-soluble phosphate and borax into water, stir at room temperature, add sodium nitrite and silicate to disperse, and obtain a rust inhibitor after drying.
2. The water-soluble quenching medium according to claim 1, characterized in that The preparation method of the rust inhibitor is as follows, in parts by weight: Add 6-8 parts of water-soluble phosphate and 2-4 parts of borax to 180-220 parts of water, stir at room temperature for 0.5-1 hour, add 4-8 parts of sodium nitrite and 2-6 parts of silicate, ultrasonically disperse for 15-30 minutes, and dry to obtain a rust inhibitor.
3. The water-soluble quenching medium according to claim 1 or 2, characterized in that: The water-soluble phosphate is one or more of sodium phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium phosphate, potassium dihydrogen phosphate, and sodium magnesium phosphate.
4. The water-soluble quenching medium according to claim 1 or 2, characterized in that: The silicate is one of sodium silicate and modified sodium silicate.
5. The water-soluble quenching medium according to claim 4, characterized in that The preparation method of the modified sodium silicate is as follows: Sodium silicate is added to water and stirred, vinyltrichlorosilane is added, oxalic acid aqueous solution is added dropwise to adjust the pH, the mixture is stirred, and concentrated and dried to obtain modified sodium silicate.
6. The water-soluble quenching medium according to claim 4 or 5, characterized in that: The preparation method of the modified sodium silicate is as follows, in parts by weight: Add 14-16 parts of sodium silicate to 200-300 parts of water and stir for 0.5-1 hour, add 4-8 parts of vinyltrichlorosilane, drop oxalic acid aqueous solution to adjust the pH to 4-5, stir at 60-70°C for 3-4 hours, concentrate and dry to obtain modified sodium silicate.
7. The water-soluble quenching medium according to claim 5 or 6, characterized in that: The oxalic acid aqueous solution is a 1-2wt% oxalic acid aqueous solution.
8. A method for preparing a water-soluble quenching medium as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The water-soluble quenching medium is obtained by mixing polyalkylene glycol, polyacrylamide, sodium polyacrylate, carboxymethyl cellulose, rust inhibitor, polypropylene glycol, Tween 80 and disodium ethylenediaminetetraacetate.
Citation Information
Patent Citations
Water-soluble quenching medium for hot die steel
CN102417955A
Quenching liquid and quenching technology for improving through quenching thickness of 50CrVA spring steel
CN102605150A